Transcriptional Read-Through Induction Treatment Trial in Intestinal Failure Induced by an EpCAM Nonsense Mutation. (9th September 2012) - Sivagnanam, Mamata; Mueller, James L.; Szigeti, Reka; Gopalakrishna, G. S.; Kellermayer, Richard
Abstract : Congenital tufting enteropathy (CTE) is a rare autosomal recessive diarrheal disorder where epithelial tufts can be present from the duodenum to the large intestine. CTE has been linked to mutations in the epithelial cell adhesion molecule gene ( EpCAM ) Sivagnanam et al. (2008). We recently reported the first case with a nonsense mutation in EpCAM Sivagnanam et al. (2010). Here, we explored the clinical and molecular effects of enterally administered gentamicin in this CTE patient. Altogether, our findings indicate that the therapy employed was insufficient to produce notable read-through induction of the EpCAM premature termination codon. This report highlights the utility of genetic testing not only in respect of diagnostics, prognostics, and family planning, but potential mutation-specific therapeutic considerations as well.